Effects of Lactobacillus casei on the expression and the activity of cytochromes P450 and on the CYP mRNA level in the intestine and the liver of male rats - Matuskova, Zuzana; Siller, Michal; Tunkova, Alena; Anzenbacherová, Eva; Zacharova, Alice; Tlaskalova-Hogenova, Helena; Zidek, Zdenek; Anzenbacher, Pavel (Neuro-endocrinology letters, 2011)
OBJECTIVES: The aim of the study was to find whether probiotic Lactobacillus casei influences the expression or the activity of cytochromes P450 (CYP) and whether it has an influence on the level of CYP mRNA in male rats. DESIGN: Live bacterial suspension of L. casei was administered orally (gavage) to healthy male Wistar rats daily for 7 days. Control group of rats was treated with the saline solution. Sections of the duodenum, jejunum, ileum, caecum and colon were dissected from each experimental animal. In all individual samples, the expression of selected CYPs was determined by Western blotting. The levels of expression of CYPs were also evaluated by mRNA using the real-time PCR method. RESULTS: There were changes observed in the expression of CYP enzymes and in the CYP mRNA levels along the intestine after application of L. casei. The expression of CYP1A1 enzyme was found to be decreased in the proximal part of the jejunum and colon, CYP1A1 mRNA level was decreased in the distal part of the jejunum, ileum and caecum. Thus, the changes in CYP1A1 protein or mRNA were observed along the intestine of male rats. Similarly, a decreased expression of the caecal CYP2E1 mRNA and of the duodenal CYP3A9 mRNA after treatment of rats with L. casei was found. CONCLUSION: Probiotic L. casei might be able to contribute to prevention against colorectal cancer by decreasing levels of certain forms of xenobiotic-metabolizing enzymes; moreover, in general, there is a possibility of interactions with concomitantly taken pharmacotherapeutic agents.
Keywords: játra; steroid-21-hydroxylasa; Lacticaseibacillus casei; cytochromy; Cytochromes; aromatické hydroxylasy; messenger RNA; střeva; regulace genové exprese enzymů; Intestines; cytochrom P-450 CYP3A; Aryl Hydrocarbon Hydroxylases; krysa rodu Rattus; zvířata; steroid-16-alfa-hydroxylasa; Cytochrome P-450 CYP2E1; Enzyme Activation; Steroid 21-Hydroxylase; potkani Wistar; Cytochrome P-450 Enzyme System; RNA, Messenger; Lactobacillus casei; Liver; Rats, Wistar; Male; cytochrom P-450 CYP2E1; Steroid 16-alpha-Hydroxylase; probiotika; Cytochrome P-450 CYP3A; Gene Expression Regulation, Enzymologic; Rats; Animals; aktivace enzymů; mužské pohlaví; Probiotics; systém (enzymů) cytochromů P-450